Doing public pastoral care through church-driven development in Africa: Reflection on church and community mobilisation process approach in Lesotho - Magezi, Vhumani (HTS teologiese studies, 2019)
African communities face various challenges that require different sectors’ interventions to be effectively addressed. Churches as key community structures in Africa along with people experience these life challenges. The situation prompts churches to continually re-examine their role in communities to develop relevant responses that are deeply rooted in Christian approaches and heritage. Pastoral care as a community frontline ministry is expected to intervene practically to address people’s holistic needs. However, the questions that emerge are the following: how can pastoral care practically be performed in a manner that it performs a public community caring role? How can public pastoral care be practically implemented? What models can be employed in providing public pastoral care? This article considers how pastoral care can be practically performed at the intersection of public theology and community development. Pastoral care performed at this intersection is termed public pastoral care. The article discusses and notes the ‘murky’ terrain and ‘apparent confusion’ on the notion of public pastoral care. Furthermore, it employs a church and community mobilisation process (CCMP) case study to progress beyond theoretical discussion to examine how public pastoral care can be operationalised in real-life situations. In doing so, it discerns the possibilities and challenges of positioning pastoral care to address public issues.